Determinants of share-based compensation plans in Central and Eastern European public companies: An institutional analysis - Marion Festing; Ihar Sahakiants (Journal for East European Management Studies, 2011)
This paper discusses the adoption of share-based compensation plans among Central and Eastern European (CEE) public companies composing major national stock exchange indices in Poland (WIG 20), the Czech Republic (PX) and Hungary (BUX). The analysis shows that the spread of such pay practices depends on the characteristics of major shareholders of the company, the state and foreign parent companies being the most prominent influencing factors. The results are discussed in the light of the legal environment in respective countries. – – Im Zentrum des vorliegenden Artikels stehen aktienbasierte Vergütungspläne in mittel- und osteuropäischen (MOE) Aktiengesellschaften, die in den nationalen Leitindizes in Polen (WIG 20), der Tschechischen Republik (PX) und Ungarn (BUX) vertreten sind. Die Analyse zeigt, dass die Verbreitung dieser Praktiken wesentlich von den Charakteristika der Hauptaktionäre der Unternehmen abhängt. Hier stellen der Staat und die ausländischen Unternehmen die wichtigsten Einflussfaktoren dar. Die Ergebnisse der Studie werden vor dem Hintergrund des regulativen Kontextes in den jeweiligen Ländern diskutiert.
Keywords: 650; Central and Eastern Europe; CEO Compensation; Comparative HRM; Institutional Environment; Ownership/Control Structures